The Kingfisher book of oceans - "Lambert, David" (Kingfisher: London, 1997)
First published in hardback in 1997, an exploration of life in the oceans, from the magic world of the coral reef to the deepest ocean trench. With more than 250 colour photographs and illustrations.
Keywords: Ocean Juvenile literature